PENGARUH STRATEGI PEMBELAJARAN EVERYONE IS A TEACHER HERE TERHADAP HASIL BELAJAR FISIKA DASAR I MAHASISWA STKIP TAPANULI SELATAN - SERI ASMAIDAH NASUTION (Jurnal Education and Development, 2017)
This research was conducted using the method of experiment. The population in this study were all students of class with a total of 14 students. The sampling technique used in this research using total sampling. For data preparation techniques X and Y variables to use observation and tests. Observation is used to capture the data variable X, and the result of the acquisition of the observations done to variable X obtained an average value of 4 that is in the category of "Very Good". The test is used to collect data variable Y, where the results of the acquisition of the results of tests performed on variable Y before use learning strategies Everyone Here Is A Teache obtained average value -rata 57.70 which is the category of "Less", while after use learning strategies everyone Here Is A Teache obtained average value of 77.44. To find out the hypothesis can be accepted or rejected by using the formula "t" test the test in order to obtain values ​​which t_hitung = 7.81 (df) = N - 2 = 32-2 = 30, t_tabel value at the 5% significance level is 1.70 , So tcount greater than ttable namely (7.81> 1.70), the null hypothesis is rejected while the alternative hypothesis is accepted